Natural history of HFE simple heterozygosity for C282Y and H63D: A prospective 12-year study - Zaloumis, S.; Allen, K.; Bertalli, N.; Turkovic, L.; Delatycki, M.; Nicoll, A.; Mclaren, C.; English, D.; Hopper, J.; Giles, G.; Anderson, G.; Olynyk, John; et al. (Blackwell Publishing, 2015)
Background and Aim - The risk of hemochromatosis-related morbidity for HFE simple heterozygosity for either the C282Y or H63D substitutions in the HFE protein was assessed using a prospective community-based cohort study. Methods - HFE genotypes were measured for 31 192 persons of northern European descent, aged between 40 and 69 years when recruited to the Melbourne Collaborative Cohort Study, and subjects were followed for an average of 12 years. For a random sample of 1438 participants stratified according to HFE genotype, two sets of biochemical iron indices performed 12 years apart and, at follow-up only, the presence/absence of six disease features associated with hereditary hemochromatosis were obtained. Summary data for 257 (139 female) C282Y simple heterozygotes and 123 (74 female) H63D simple heterozygotes were compared with 330 (181 female) controls with neither HFE mutation. Results - At baseline, mean transferrin saturation (TS) (95% confidence interval) and prevalence of TS > 55% were 35.14% (33.25, 37.04) and 3/112 (3%), 33.03% (29.9, 36.15) and 0/39 (0%), and 29.67% (27.93, 31.4) and 3/135 (2%) for C282Y, H63D and wild-type male participants, respectively. At follow-up, mean TS levels remained similar to baseline levels for both men and women irrespective of simple heterozygosity for either mutation. No HFE C282Y or H63D simple heterozygotes had documented iron overload (based on hepatic iron measures or serum ferritin greater than 1000 mg/L at baseline with documented therapeutic venesection). Conclusion - No documented iron overload was observed for HFE simple heterozygotes for either C282Y or H63D, and morbidity for both HFE simple heterozygote groups was similar to that of HFE wild-type participants.